The Role of the Family in Cultivating Islamic Moderation Value to Early Childhood - Dian Eka Priyantoro; Alvin Ma'viyah; Na'im Hidayaturrohmah; Atin Risnawati; Diaz Maulidya (Jurusan PGMI FTIK IAIN Metro Lampung, 2020)
This paper aimed to explain the families’ role in instilling the moderation of Islam to early childhood. This was a library research in nature, exposing the role of families towards the planting of Islamic moderation values to early childhood by analyzing scholarly works in the form of journal articles and books related to the issue in question. The results of this study show that families, especially parents, play an important role in educating children by instilling moderation in Islam early on so that the child can be away from the phenomenon of religious radicalism. Early childhood is an early impersonator because the age of the child is in the golden age or commonly known as the sensitive age of the child receiving stimulation. The role of families in introducing the value of islamic moderation early on to children can be done in simple things such as, invite the child to see the film upin and ipin which tells how together they live together between ethnic, religious, racial, and intersle class (SARA) films.